EMQN best practice guidelines for the molecular genetic diagnosis of hereditary hemochromatosis (HH) - Porto, Graça (Eur J Hum Genet, 2016)
Molecular genetic testing for hereditary hemochromatosis (HH) is recognized as a reference test to confirm the diagnosis of suspected HH or to predict its risk. The vast majority (typically >90%) of patients with clinically characterized HH are homozygous for the p.C282Y variant in the HFE gene, referred to as HFE-related HH. Since 1996, HFE genotyping was implemented in diagnostic algorithms for suspected HH, allowing its early diagnosis and prevention. However, the penetrance of disease in p.C282Y homozygotes is incomplete. Hence, homozygosity for p.C282Y is not sufficient to diagnose HH. Neither is p.C282Y homozygosity required for diagnosis as other rare forms of HH exist, generally referred to as non-HFE-related HH. These pose significant challenges when defining criteria for referral, testing protocols, interpretation of test results and reporting practices. We present best practice guidelines for the molecular genetic diagnosis of HH where recommendations are classified, as far as possible, according to the level and strength of evidence. For clarification, the guidelines' recommendations are preceded by a detailed description of the methodology and results obtained with a series of actions taken in order to achieve a wide expert consensus, namely: (i) a survey on the current practices followed by laboratories offering molecular diagnosis of HH; (ii) a systematic literature search focused on some identified controversial topics; (iii) an expert Best Practice Workshop convened to achieve consensus on the practical recommendations included in the guidelines.